Lecture notes. Orthopaedics and fractures - Duckworth, T.; Blundell, C. M. (Chris M.); Duckworth, T.; Wiley InterScience (Online service) (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2010)
'Providing a concise approach to the subject, the new edition of Lecture Notes: Orthopaedics and Fractures reflects recent changes to medical education and includes new management techniques. Divided into two major sections, General Principles covers form and function, fractures, trauma and musculoskeletal disorders, while Regional Orthopaedics covers the examination of and conditions affecting individual regions of the body, e.g. foot and ankle, spine and trunk. This ensures the content is integrated to allow better and easier navigation.''Featuring an extensive collection of X-rays and photographs of orthopaedic conditions, Lecture Notes: Orthopaedics and Fractures is ideal for medical students, junior doctors, nurses or allied health professionals who want a core introduction to this important specialty.'--Jacket.
Musculoskeletal structures and function -- Soft tissue injuries and healing -- Nerve injuries and repair -- Fractures and healing -- Fractures : principles of management -- Complications of fractures -- Major trauma -- Congenital malformations -- Generalised orthopaedic conditions -- Inflammatory conditions -- Degenerative conditions -- Neoplastic conditions of bone and soft tissue -- Infections -- Metabolic diseases of bone -- Examination of the musculoskeletal system -- The forearm, wrist, and hand -- The elbow -- The shoulder and upper arm -- The spine -- The pelvis -- The hip and thigh -- The knee and lower leg -- The foot and ankle -- Orthopaedic techniques.
Revised edition of: Lecture notes on orthopaedics and fractures / T. Duckworth. 3rd ed. c1995.
Includes index.
Print version record.
Keywords: Orthopedics -- Handbooks, manuals, etc; Fractures -- Handbooks, manuals, etc; Orthopedic Procedures; Fractures, Bone; Ortopèdia.; Fractures; Handbooks; Electronic books; Handbooks and manuals